Europium-doped MnO2 nanostructures for controlling optical properties and visible light photocatalytic activity. (2022) - Panimalar, S.; Chandrasekar, M.; Logambal, S.; Uthrakumar, R.; Inmozhi, C.
Abstract: Pure and europium (Eu) doped manganese oxide (MnO2 ) photocatalysts were produced using a simple sol-gel technique, and their physical, anatomical, and optical characteristics were extensively studied by means of XRD, TEM, EDAX, Raman, UV, PL, and N2 adsorption-desorption analysis. The energy band gap and degree of crystallinity of Eu-doped MnO2 changed with the presence of Eu. The Eu-doped MnO2 XRD pattern revealed a hexagonal surface morphology with an typical particle size of 30 nm. The occurrence of trivalent europium and its effective doping into the crystalline structure of MnO2 matrix were validated using the EDS method. The catalytic efficiency of Eu-doped MnO2 for methyl orange decomposition was investigated. Under infrared spectrum, photocatalytic studies revealed that phenol was degraded over a Eu doped MnO2 sample in 100 min (464 nm). The enhanced photocatalytic response by Eu doping was also thoroughly addressed.